The neoadjuvant immunotherapy for non-metastatic mismatch repair-deficient colorectal cancer: a systematic review - Cui, Hong-Xia; Yang, Xiao-Quan; Zhao, Guang-yue; Wang, Feng-jian; Liu, Xin (Frontiers in Immunology, 2025)
BackgroundImmunotherapy has become the first-line treatment for metastatic mismatch repair deficient (dMMR) colorectal cancer. The efficacy and safety of neoadjuvant immunotherapy for the treatment of non-metastatic dMMR colorectal cancer remain unclear. In this article, we explore the clinical effect and safety of neoadjuvant immunotherapy for non-metastatic dMMR colorectal cancer.MethodsWe collected clinical data from the databases (PubMed, Wanfang Embase, Cochrane Library, and China National Knowledge Infrastructure databases) up to November 2024. The primary outcomes of major pathological response (MPR), pathological complete response (pCR), and other outcomes were analyzed for the final results. The secondary outcomes (pCR rates for the subgroups) were also analyzed.ResultsWe included 21 articles with 628 non-metastatic dMMR colorectal cancers. A pCR was found in 320/480 (66.6%) patients [effect size (ES): 0.70, 95% CI: 0.66 to 0.74] with the fixed-effects model and little heterogeneity. A MPR was found in 388/452 (85.8%) patients (ES: 0.86, 95% CI: 0.81 to 0.91) with the fixed-effects model and little heterogeneity. In the subgroup analysis, pCR rates were similar in the T1-T3 group and T4a-T4b group in the fixed-effects model with minimal heterogeneity (OR: 0.76, 95% CI: 0.48 to 1.22). The pCR rates were similar in the colon cancer group and rectal cancer group in the fixed-effects model with minimal heterogeneity (OR: 1.41, 95% CI: 0.39 to 5.12). Similar pCR rates were found in the immune monotherapy group and immune therapy plus chemotherapy group (OR: 0.74, 95% CI: 0.26 to 2.10) with the fixed-effects model and little heterogeneity.ConclusionNeoadjuvant immunotherapy achieves high rates of pCR and MPR for non-metastatic dMMR colorectal cancer. For locally advanced T4 stage dMMR colorectal cancer, neoadjuvant immunotherapy can still achieve good pCR rates. Neoadjuvant immune monotherapy can achieve good pCRs rates, avoiding the toxic side effects caused by combined dual immunotherapy and chemo(radio)therapy. Neoadjuvant immunotherapy could be another treatment option for non-metastatic dMMR colorectal cancer.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024594173.